The chronometry of risk processing in the human cortex - Symmonds, Mkael; Moran, Rosalyn J.; Wright, Nicholas D.; Bossaerts, Peter; Barnes, Gareth; Dolan, Raymond J. (Frontiers in Neuroscience, 2013)
The neuroscience of human decision-making has focused on localising brain activity correlating with decision variables and choice, most commonly using functional MRI. Poor temporal resolution means these studies are agnostic in relation to how decisions unfold in time. Consequently, here we address the temporal evolution of neural activity related to encoding of risk using magnetoencephalography (MEG), and show modulations of electromagnetic power in posterior parietal and dorsomedial prefrontal cortex which scale with both variance and skewness in a lottery, detectable within 500ms following stimulus presentation. Electromagnetic responses in somatosensory cortex following this risk encoding predict subsequent choices. Furthermore, within anterior insula we observed early and late effects of subject-specific risk preferences, suggestive of a role in both risk assessment and risk anticipation during choice. The observation that cortical activity tracks specific and independent components of risk from early time-points in a decision making task supports the hypothesis that specialised brain circuitry underpins risk perception.